Dietary Substitution Effect of Fishmeal with Tunic Meal of Sea Squirt, Halocynthia roretzi, Drasche, on Growth and Soft Body Composition of Juvenile Abalone, Haliotis discus, Reeve 1846. Issue 6 (28th May 2018) - Choi, Dong Gyui; Kim, June; Yun, Ahyeong; Cho, Sung Hwoan; Jeong, Hae Seung; Lee, Ki Wook; Kim, Hee Sung; Kim, Pil Youn; Ha, Min Su
Abstract: The dietary substitution effect of fishmeal (FM) with tunic meal of sea squirt (SS) on growth and body composition of juvenile abalone, Haliotis discus, was evaluated. A total of 1470 juvenile abalone were distributed into 21 70‐L plastic rectangular containers. Six experimental diets in triplicate were prepared, and 20% FM was included in the FM0 diet. The treatments consisted of 20, 40, 60, 80, and 100% of FM substituted with tunic meal of SS, referred to as the FM20, FM40, FM60, FM80, and FM100 diets, respectively. Undaria was also prepared to compare the effect of the formulated diets on performance of abalone. The experimental diets were fed to abalone once a day at a satiation level for 16 wk. Weight gain of abalone fed the FM0 diet was higher than that of abalone fed the FM100 diet and Undaria, but not different from that of abalone fed the FM80 diet. Crude protein, crude lipid, and ash contents of the soft body of abalone fed all formulated diets were higher than those of abalone fed the Undaria diet. In conclusion, FM up to 80% could be replaced with tunic meal of SS without retardation in growth of abalone. The best growth was obtained in abalone fed the FM20 diet.